Performance of rice under agrisilvicultural system in terai zone of West Bengal - Panwar, Pankaj; Chakravarty, Sumit (Indian Journal of Agroforestry, 2020)
Three rice based agrisilviculture systems were established in terai zone of West Bengal to find out the compatibility of trees under paddy based land use system. The trees were spaced at two spacing (6x6m and 6x3 m) to find out the effect of spacing on the performance of paddy. Observation on yield attributes, PAR and LAI were taken. It was found that Salix tetrasperma was the best tree out of the three tree species taken as its canopy allowed more PAR above paddy (1305.11 µmol s-1 m-2 ) to penetrate and had less LAI (2.78). As a result the yield of paddy was more (3.79 t/ha). Higher yield of paddy was also observed as the distance from the tree increased in all land use system. The best combination of species and distance from tree was Salix tetrosperma (6 x 6 m) at 3 m distance from the tree as the highest yield was4.01 t/ha., PAR above paddy (1383.66 µmol s-1 m-2) and lowest LAI (2.18).